1931 Ill. Laws 454 - (:unkn) unknown (My University, 1931)
An Act to Regulate the Sale, Possession and Transportation of Machine Guns, § 7: Prohibited being armed with a machine gun while committing arson, assault, burglary, kidnapping, larceny, rioting, or robbery. Punishable by imprisonment for 5 years to life.
Keywords: CARRY - INTENT TO COMMIT CRIME; MACHINE GUN RESTRICTION